Pharmacokinetics of Azlocillin in Persons with Normal and Impaired Renal Functions - Fiegel, P. (Antimicrob Agents Chemother, 1978)
The pharmacokinetics of azlocillin, a new wide-spectrum antibiotic of the N-substituted group of ureidomethyl penicillins, was investigated in 10 subjects with normal and in 32 subjects with impaired renal functions. After intravenous injection of 2 g of azlocillin, serum concentrations of drug were measured microbiologically. The half-lives of azlocillin were 47 ± 8.8 min in patients with normal renal function, and 293.3 min in patients with severely impaired renal function. The correlation of half-life to renal functions is shown by the equation: t/2 = 425.03·Cl(In)(−0.4509), where Cl(In) is inulin clearance. The volume of distribution of the azlocillin was 17.7% of the body weight. Protein binding was similar in patients with normal renal function and in those with severely impaired renal functions. The urinary excretion rate of azlocillin in patients with normal renal function was 64.8 ± 8.8% in 24 h.